2001
DOI: 10.1099/00207713-51-4-1361
|View full text |Cite
|
Sign up to set email alerts
|

Simplified technique for identification of the aerobic spore-forming bacteria by phenotype.

Abstract: The use of modern research approaches of genetics, biochemistry and molecular biology has led to progress in bacterial taxonomy. Systematic study of the aerobic spore-forming bacteria has resulted in the realignment of the genus Bacillus into several new genera. In the meantime, the identification process has become more difficult for the non-specialist in Bacillus taxonomy. This paper presents a key for the simplified phenotypic identification of the mesophilic, aerobic, spore-forming bacteria belonging to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 66 publications
0
23
0
4
Order By: Relevance
“…Gram-negative isolates from PCA and VRBGA plates were also tested for behaviour in TSI (triple sugar iron agar, Microbiol), then grouped according to the criteria of Mossel, Corry, Struijk, and Baird (1995) and identified by API 20E and API 20NE (bioMérieux, Marcy l'Etoile, France). Aerobic spore-forming bacteria were identified according to Claus and Berkeley (1986), and Reva, Sorokulova, and Smirnov (2001), and the identification confirmed by using the API 50 CHB galleries (bioMérieux). Gram-positive, catalase-negative isolates from M17 and MRS agar plates were tested for growth at 10, 15 and 45°C in 4 and 6.5% NaCl, gas production from glucose (MRS broth with inverted Durham tubes) and production of NH 3 from arginine, as described by Schillinger and Lücke (1987).…”
Section: Isolation and Identification Of Microorganismsmentioning
confidence: 99%
“…Gram-negative isolates from PCA and VRBGA plates were also tested for behaviour in TSI (triple sugar iron agar, Microbiol), then grouped according to the criteria of Mossel, Corry, Struijk, and Baird (1995) and identified by API 20E and API 20NE (bioMérieux, Marcy l'Etoile, France). Aerobic spore-forming bacteria were identified according to Claus and Berkeley (1986), and Reva, Sorokulova, and Smirnov (2001), and the identification confirmed by using the API 50 CHB galleries (bioMérieux). Gram-positive, catalase-negative isolates from M17 and MRS agar plates were tested for growth at 10, 15 and 45°C in 4 and 6.5% NaCl, gas production from glucose (MRS broth with inverted Durham tubes) and production of NH 3 from arginine, as described by Schillinger and Lücke (1987).…”
Section: Isolation and Identification Of Microorganismsmentioning
confidence: 99%
“…An identification key proposed previously [27] was used for identification. This key is represented on-line at the following website http://www.imv.kiev.ua/key/.…”
Section: Phenotypic Characterization Of Bacillus Probiotic Strainsmentioning
confidence: 99%
“…The use of phenotypic characteristics, although classical, has been successfully used in the identification of the aerobic spore-forming bacteria (Reva et al 2001). Analyses showed that some isolates possessed a number of characteristics quite different from those of their type strains, suggesting that those isolates were misclassified.…”
Section: Taxonomic Reassessmentmentioning
confidence: 99%